Southern folk medicine, 1750-1820 - Moss, Kay. (Columbia, S.C. : University of South Carolina Press, 1999)
The author "inventories the medical ingredients and practices adopted by physicians, herb women, yeoman farmers, plantation mistresses, merchants, tradesmen, preachers, and quacks alike ... [and] shows how families passed down cures as heirlooms, how remedies crossed cultural and ethnic boundaries, and how domestic healers compounded native herbs and plants with exotic ingredients."--Jacket.
Ch. 12. Nervous diseases -- Ch. 13. Surgery -- Ch. 14. Sympathetic medicine: signs, charms, incantations, and spells -- pt. 3: A domestic materia medica -- Introduction -- Key to sources -- Simples and medicinal preparations fit for home practice -- Appendixes: A. Weights and measures -- B. Classes of medicinal preparations -- C. The southern frontier and the eighteenth century -- D.A blaze of medical knowledge: The eighteenth century -- E. The professional practitioner: physician, surgeon, preacher, or quack.
Includes bibliographical references (pages 245-250) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Traditional medicine -- Southern States -- History; Traditional medicine -- Southern States -- Formulae, receipts, prescriptions; Medicine, Popular -- Formulae, receipts, prescriptions; Folklore -- Southern States; Southern States -- Social life and customs; Folklore; Medicine, Traditional -- history; Folklore; Formularies as Topic; Southeastern United States; Médecine traditionnelle -- États-Unis (Sud) -- Histoire; Médecine traditionnelle -- États-Unis (Sud) -- Formules et recettes; Médecine traditionnelle -- États-Unis (Sud) -- Formules et recettes -- Ouvrages de vulgarisation; Folklore -- États-Unis (Sud); États-Unis (Sud) -- Mœurs et coutumes; Médecine -- Ouvrages de vulgarisation -- Formules et recettes; Folklore; folklore (culture-related concept); PSYCHOLOGY -- Psychotherapy -- General; Folklore; Manners and customs; Medicine, Popular; Traditional medicine; Southern States; History; Prescriptions, formulae, receipts, etc